2016
DOI: 10.1007/s00122-016-2668-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping of powdery mildew resistance gene Pm21 and functional characterization of resistance-related genes in wheat

Abstract: The powdery mildew resistance gene Pm21 was physically and comparatively mapped by newly developed markers. Seven candidate genes were verified to be required for Pm21 -mediated resistance to wheat powdery mildew. Pm21, a gene derived from wheat wild relative Dasypyrum villosum, has been transferred into common wheat and widely utilized in wheat resistance breeding for powdery mildew. Previously, Pm21 has been located to the bin FL0.45-0.58 of 6VS by using deletion stocks. However, its fine mapping is still a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…VIGS systems based on BSMV vectors that can silence genes in barley and wheat have been developed, but as mentioned in the section “Introduction” they have several limitations (Holzberg et al, 2002; Bruun-Rasmussen et al, 2007; Meng et al, 2009; Yuan et al, 2011; Chen et al, 2015; Jiao et al, 2015; Wang et al, 2015; Zhang et al, 2015; He et al, 2016). Moreover, the only VIGS tools for maize do not function at the whole-plant level, because they only lead to partial photo-bleaching when they are used to silence PDS in maize leaves (Ding et al, 2006; Liu et al, 2016; Mei et al, 2016; Wang R. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VIGS systems based on BSMV vectors that can silence genes in barley and wheat have been developed, but as mentioned in the section “Introduction” they have several limitations (Holzberg et al, 2002; Bruun-Rasmussen et al, 2007; Meng et al, 2009; Yuan et al, 2011; Chen et al, 2015; Jiao et al, 2015; Wang et al, 2015; Zhang et al, 2015; He et al, 2016). Moreover, the only VIGS tools for maize do not function at the whole-plant level, because they only lead to partial photo-bleaching when they are used to silence PDS in maize leaves (Ding et al, 2006; Liu et al, 2016; Mei et al, 2016; Wang R. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is rarely reported that TRV-VIGS was used in monocot plant species, especially in wheat and maize. Barley stripe mosaic virus (BSMV)-mediated VIGS (BSMV-VIGS) is a useful tool for gene functional analysis in cereals that has been widely used in monocot plant research, but high-efficiency depended on microprojectile bombardment instruments or in vitro transcript or pre-infiltration of Nicotiana benthamiana , (Meng et al, 2009; Wang et al, 2011, 2015; Yuan et al, 2011; Chen et al, 2015; Jiao et al, 2015; Zhang et al, 2015; He et al, 2016) which limited its application. VIGS tools for maize is lacking, except the VIGS vectors derived from brome mosaic virus (BMV) (Ding et al, 2006) and recently reported virus vectors based on cucumber mosaic virus (CMV) strain ZMBJ-CMV and foxtail mosaic virus (FoMV) (Liu et al, 2016; Mei et al, 2016; Wang R. et al, 2016), however, the photo-bleaching symptom by silencing phytoene desaturase (PDS) gene is partial, suggesting that those VIGS systems in maize could not function at whole-plant level.…”
Section: Introductionmentioning
confidence: 99%
“…In response to pathogen infection, plants can trigger various rapid and inducible defence responses, which function at different stages and to different degrees after pathogens contact the plant (Nomura et al, 2005;Schoonbeek et al, 2015;Stam et al, 2014;Talarczyk and Hennig, 2001). In plants with a resistant phenotype, the early recognition of pathogen effectors by the host resistance (R) proteins triggers a race-specific resistance, such as gene-for-gene resistance, which is often accompanied by the hypersensitive response (HR) and can provide a higher level of resistance against a few pathogen species (Ding et al, 2017;Hammond-Kosack and Jones, 1996;He et al, 2016;Kumar and Kirti, 2015). The roles of the phytohormones salicylic acid (SA) and jasmonic acid (JA) in the regulation of these inducible defences have been well established (Shen et al, 2017;Thaler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FL0.45-0.58 carrying Pm21, were reported to be required by Pm21 resistance He et al 2016); however, due to lack of a fine map, the relationships of these candidate genes and Pm21 are unclear.…”
mentioning
confidence: 99%
“…1B, 1C and 1D). Subsequently, a 17,732-bp genomic sequence harboring three complete genes, viz., DvPP2C, encoding a protein phosphatase (He et al 2016), DvRGA2 and DvRGA1, were obtained together with a separated gene DvRGA3 from the resistant D. villosum line DvRes-1 by PCR ( Fig. S3).…”
mentioning
confidence: 99%